2-Phenylacetic acid–3-{(E)-2-[(E)-pyridin-3-ylmethylidene]hydrazin-1-ylidenemethyl}pyridine (2/1) - Edward R. T. Tiekink (Acta Crystallographica Section E, 2010)
The asymmetric unit of the title 1:2 adduct, C12H10N4·2C8H8O2, comprises a single molecule of 2-phenylacetic acid and half a molecule of 3-pyridinealdazine; the latter is completed by crystallographic inversion symmetry. In the crystal, molecules are connected into a three-component aggregate via O—H...N hydrogen bonds. As the carboxyl group lies above the plane through the benzene ring to which it is attached [C—C—C—C = 62.24 (17)°] and the 4-pyridinealdazine molecule is almost planar (r.m.s. deviation of the 16 non-H atoms = 0.027 Å), the overall shape of the aggregate is that of a flattened extended chair. Layers of these aggregates are connected by C—H...O and C—H...π interactions and stack parallel to (220).